Sehat Sahulat Program Effect on Patients Presenting to Secondary Level Hospital in Mardan - Ammad Ali; Saad Ali; Irsa Hidayat; Muhammad Ayub; Faiza Akbar; Ahsan Ali; Mashal Tamsil (Gandhara University, 2022)
OBJECTIVES The aim was to find the difference between government and private hospitals at the Mardan secondary level for sehat sahulat card effect on patients for their selection of hospital, dates, and time issues for elective and emergency cases with department facilities. METHODOLOGY This quantitative cross-sectional study was conducted to see the difference between the government and private hospitals for sehat the sahulat program effect on patients. Patients care is important on both sides but to find out the difference where more work should be done to achieve universal global health under the Khyber Pakhtunkhwa government for the benefit of their people's health. RESULTS Total patients 10112 visited District Head Quarter (DHQ) hospital from February 2021 to February 2022 while 5672 were in a private hospital in which the ratio for gynaecology was 19 % (854 pts. DHQ) and 31% (1652) private hospital. Medical admissions were 2224 (50%) for a government hospital and none for private while surgical admissions were 1379 (31%) for government and 2665 (50%) for private hospitals. The significant ratio for chi-sq was P<0.5 CONCLUSION Government hospital flow of patients is more than the private sector in admission ratio for medical cases then surgical while private has more flow for surgical admission than medical with all facilities provided on the desk and timely managed at the time of admission. Seniorm consultant's ratio of surgeries in private is more than in government hospitals.